Diversity of Termitomyces Associated with Fungus- Farming Termites Assessed by Cultural and Culture- Independent Methods - Makonde, H.M.; Boga, Hamadi I.; Osiemo, Z.; Mwirichia, Romano K.; Stielow, J.B.; Go¨ ker, Markus; et al. (My University, 2013)
Background: Fungus-cultivating termites make use of an obligate mutualism with fungi from the genus Termitomyces, which are acquired through either vertical transmission via reproductive alates or horizontally transmitted during the formation of new mounds. Termitomyces taxonomy, and thus estimating diversity and host specificity of these fungi, is challenging because fruiting bodies are rarely found. Molecular techniques can be applied but need not necessarily yield the same outcome than morphological identification. Methodology: Culture-dependent and culture-independent methods were used to comprehensively assess host specificity and gut fungal diversity. Termites were identified using mitochondrial cytochrome oxidase II (COII) genes. Twenty-three Termitomyces cultures were isolated from fungal combs. Internal transcribed spacer (ITS) clone libraries were constructed from termite guts. Presence of Termitomyces was confirmed using specific and universal primers. Termitomyces species boundaries were estimated by cross-comparison of macromorphological and sequence features, and ITS clustering parameters accordingly optimized. The overall trends in coverage of Termitomyces diversity and host associations were estimated using Genbank data. Results and Conclusion: Results indicate a monoculture of Termitomyces in the guts as well as the isolation sources (fungal combs). However, cases of more than one Termitomyces strains per mound were observed since mounds can contain different termite colonies. The newly found cultures, as well as the clustering analysis of GenBank data indicate that there are on average between one and two host genera per Termitomyces species. Saturation does not appear to have been reached, neither for the total number of known Termitomyces species nor for the number of Termitomyces species per host taxon, nor for the number of known hosts per Termitomyces species. Considering the rarity of Termitomyces fruiting bodies, it is suggested to base the future taxonomy of the group mainly on well-characterized and publicly accessible cultures.